Localized removal affects white‐tailed deer space use and contacts. Issue 1 (30th September 2016) - Tosa, Marie I.; Schauber, Eric M.; Nielsen, Clayton K.
ABSTRACT: Transmission and impact of infectious diseases can be altered if host social structure is disrupted by disease outbreaks or lethal management. Specifically, if remnants of depopulated groups join or increase contact with neighboring groups, between‐group transmission may increase even as population density decreases. We tested whether this phenomenon could apply to diseases of white‐tailed deer ( Odocoileus virginianus ) by using a before‐after‐control‐impact design. We monitored space use and contacts among adult female and juvenile deer in southern Illinois during 2011–2014; midway through each study season, we removed all members except 1 collared deer from centrally located groups and left control groups intact. After group removal, remnant adult females shortened duration of contacts with neighboring groups, whereas remnant juveniles responded with greater shifts in space use and appeared to join neighboring groups. Together, our study points to potential age‐specific responses of deer to social disruption, with evidence that juveniles respond in ways that could shift disease transmission dynamics toward frequency dependence. These findings highlight the need for focused research into the importance of social disruption in disease dynamics, and lend support for complete group removal (if possible) when culling for disease management. © 2016 The Wildlife Society. Abstract : Transmission and impact of infectious diseases can be altered if host social structure is disrupted. By testing whether remnant white‐tailed deer join or increase contacts with neighboring groups after group depopulation, we found age‐specific responses to social disruption and support for complete group removal when culling for disease management.